Food poisoning outbreak in prisoners - Khalid Abdullah, Mazin; Qader Salman, Marwa; Mahmood Rajab, Ibraheem (Diyala Journal of Medicine, 2023)
Background: An outbreak of food poisoning was investigated in a prison in AL-Muradia area in Diyala in June 23, after poisoning cases was reported to the primary health care center of the area on June 22, 2022. Objective: To determine the cause of food poisoning outbreak among the inmates. Patients and Methods: A retrospective cohort study was conducted in a prison in AL-Muradia area in Diyala in June 23 and the data has been collected using a questionnaire developed by the researcher and filled out by direct interview with all individuals who attended meals, all person in that prison were interviewed and traced back every meal served in the last two days before the investigation. Results: All people who had interviewed, (12) reported to have a common meal in afternoon of 21-June 2022, with age mean of 33.5+_ 6 SD. (5) of them met the probable case definition of food poisoning, and the first two cases had the onset of symptoms within 12hr. of the exposure, the last case experienced a symptom was after 24 hr., all cases had fever and headache followed by diarrhea (80%), nausea and abdominal pain (60%) and vomiting (40%). The meal items were canned meat, canned tuna, grilled chicken, apricot, plum and yogurt, the highest relative risk was for tuna (RR=4) with risk difference of (50%) Conclusion: The food item responsible for the outbreak was canned tuna. Based on the incubation period, symptoms and the unhealthy storage of food suggested that canned tuna could be contaminated with salmonella spp.